1988
DOI: 10.1111/j.1467-2494.1988.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Photostability assessment of sunscreens. Benzylidene camphor and dibenzoylmethane derivatives

Abstract: Synopsis A rapid method has been developed in order to compare the photostability of several sunscreen agents incorporated in the same type of emulsion. Thin films of the different preparations were spread on quartz plates and irradiated with a solar simulator. Differences in energy distribution according to wavelengths observed with solar simulator and sun radiation were taken into account. A kinetic study of absorption properties was carried out under solar simulator irradiation. A simple calculation gave th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 10 publications
1
63
0
Order By: Relevance
“…It is able to absorb UV photons and it has been shown to improve the photostability of sunscreen formulations containing the combination octyl methoxycinnamate/avobenzone (Chaudhuri et al, 2006). Photostability evaluation studies are usually performed using quantitative separation techniques as High Performance Liquid Chromatography (HPLC) Deflandre and Lang, 1988;Berset et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is able to absorb UV photons and it has been shown to improve the photostability of sunscreen formulations containing the combination octyl methoxycinnamate/avobenzone (Chaudhuri et al, 2006). Photostability evaluation studies are usually performed using quantitative separation techniques as High Performance Liquid Chromatography (HPLC) Deflandre and Lang, 1988;Berset et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…4-MBC is classified as an UV-B filter since it absorbs most efficiently in the 290-320 nm range and it is included in the list of authorized UV filters in Europe, Australia and is being considered for use in the USA [10]. Although 4-MBC has been regarded as rather photostable [6,11], recent studies have demonstrated that this sunscreen agent undergoes marked degradation under sunlight exposure [12,13]. Therefore, new systems with enhanced 4-MBC photostability are required.…”
Section: Introductionmentioning
confidence: 99%
“…The suitable filter was worked out based on extensive photochemical investigations to identify the structural requirements for optimal absorption and relaxation of absorbed quantum energy. 17,21,22,26 Terephthalylidene dicamphor sulfonic acid (Mexoryl SX, [Chimex SA, France] USAN: ecamsule) 25 containing either 2% avobenzone (A) or 2% avobenzone and 10% octocrylene (B) were spread on roughened quartz plates and exposed to 30 J/cm 2 ultraviolet-A. After exposure, films were solubilized in ethanol and residual content of avobenzone was determined by high-performance liquid chromatography.…”
Section: Development Of a Short Uva Filtermentioning
confidence: 99%
“…This has permitted assessment of the stability of the protection level over time under UV exposure. 17 A solar simulator that sends out a light mimicking sunlight was used and equipped to expose sunscreen preparations to solar UVR spectrum. The light transmitted through the irradiated sample was analyzed and the amount measured throughout the trial.…”
Section: Steps Toward More Efficient Sunscreensmentioning
confidence: 99%
See 1 more Smart Citation